Knockdown of Endogenous Nucb2/Nesfatin-1 in the PVN Leads to Obese-Like Phenotype and Abolishes the Metformin- and Stress-Induced Thermogenic Response in Rats - Stephan, Daniel; Taege, Natalie; Dore, Riccardo; Folberth, Julica; Jöhren, Olaf; Schwaninger, Markus; Lehnert, Hendrik; Schulz, Carla (Hormone and Metabolic Research, 2022)
Nesfatin-1, the cleavage product of nucleobindin-2, is an anorexigenic peptide and major regulator of energy homeostasis. Beyond reducing food intake and increasing energy expenditure, it is also involved in regulating the stress response. Interaction of nucleobindin-2/nesfatin-1 and glucose homeostasis has been observed and recent findings suggest a link between the action of the antidiabetic drug metformin and the nesfatinergic system. Hence, this study aimed to clarify the role of nucleobindin-2/nesfatin-1 in the paraventricular nucleus of the hypothalamus in energy homeostasis as well as its involvement in stress- and metformin-mediated changes in energy expenditure. Knockdown of nucleobindin-2/nesfatin-1 in male Wistar rats led to significantly increased food intake, body weight, and reduced energy expenditure compared to controls. Nucleobindin-2/nesfatin-1 knockdown animals developed an obese-like phenotype represented by significantly increased fat mass and overall increase of circulating lipids. Concomitantly, expression of nucleobindin-2 and melanocortin receptor type 3 and 4 mRNA in the paraventricular nucleus was decreased indicating successful knockdown and impairment at the level of the melanocortin system. Additionally, stress induced activation of interscapular brown adipose tissue was significantly decreased in nucleobindin-2/nesfatin-1 knockdown animals and accompanied by lower adrenal weight. Finally, intracerebroventricular administration of metformin significantly increased energy expenditure in controls and this effect was absent in nucleobindin-2/nesfatin-1 knockdown animals. Overall, we clarified the crucial role of nucleobindin-2/nesfatin-1 in the paraventricular nucleus of the hypothalamus in the regulation of energy homeostasis. The nesfatinergic system was further identified as important mediator in stress- and metformin-induced thermogenesis.
Keywords: energy homeostasis; obesity; metabolic syndrome; oral antidiabetic drugs; OAD; diabetes; hypothalamus; NTS; brown adipose tissue